The Weight-loss Practices of Judoka - Coles, D.
In order to assess the frequency, magnitude and methods of weight-loss, 165 judoka (male n = 123, average age 29 years and female n = 42, average age 22 years) completed a questionnaire relating to their weight-loss practices. A summary of the main findings, some observations and recommendations are presented below. 86% of judoka reported that they have deliberately lost weight in order to make their fighting weight. The largest amount of weight loss reported - 20 kg. Average weight lost in order to make fighting weight - 4.0 kg. Average time judoka allow to make weight - 15 days. Average age judoka started losing weight - 16 years. 59% engaged in weight loss activities whilst under the age of sixteen. Twelve of the judoka reported losing weight between the ages of 8 and 10. The most commonly used weight loss method reported by 96% of the judoka was cutting out snacks. 82% used more aerobic exercise, 81% skipped meals and 78% exercised in sweat kit. 62% of judoka reported the use of fluid restriction, and 47% reported going without food or fluid for periods of over 24 hours. The use of laxatives was reported by 6% of the subjects, diuretics 3%, self induced vomiting 5% and diet pills 1%. Statistical analysis revealed the frequency, magnitude and methods of weight loss utilised by judoka, is the same as, or in excess of American Collegiate wrestlers. Observations Weight losses of no more than 0.9 kg per week are recommended as being reasonably safe and effective under the right circumstances. The rapid weight loss regimes used by judoka will almost certainly lead to decreases in judo performance. In 1997 three American Collegiate wrestlers died whilst trying to make their weight. Weight loss by children can result in adverse effects on normal patterns of growth and development. The use of laxatives, diuretics, self induced vomiting, and diet pills may lead to eating disorders such as anorexia and bulimia. Recommendations The findings of the study indicate the need for the greater education of judoka, coaches and judokas` parents regarding weight loss. The promotion of sound nutrition in order to facilitate normal health and growth, and to elicit peak performance is also recommended. The introduction of legislative measures, on par with those implemented in American wrestling, may go someway to alleviating the problem. However, it is recognised that such legislation is difficult to enforce. It would appear therefore, that the weight loss practices that have been utilised by judoka for many years will probably continue to be an integral part of the sport.